First observations of coral spawning at the Banda Islands, Maluku, Indonesia - ANDIKA NOVRIANSYAH; MAREIKE HUHN; HERDIAN WICAKSONO; BUDIONO SENEN; BEGINER SUBHAN; DOUGLAS FENNER; HAWIS MADDUPPA; P. JOANA DIAS (Society for Indonesian Biodiversity, 2023)
Abstract. Novriansyah A, Huhn M, Wicaksono H, Senen B, Subhan B, Fenner D, Madduooa H, Dias PJ. 2023. First observations of coral spawning at the Banda Islands, Maluku, Indonesia. Biodiversitas 24: 6082-6091. Due to their high diversity and productivity, their socio-economic value to coastal communities and their crucial role in coastal protection, coral reefs belong to the most important marine ecosystems in the world. Understanding and protecting coral reefs has never been so important, given the unprecedented anthropogenic pressures they face. Indonesia holds 18% of the world’s coral reefs and is home to some of the richest marine biodiversity on the planet. However, with over 17,000 islands scattered across 86,700 km2, marine monitoring and conservation remains challenging. The Banda Sea (Maluku, Indonesia) ecoregion ranks as a high priority for marine conservation. The present study reports on the first observations of coral spawning at the Banda Islands from 2016 to 2019. Ad-hoc opportunistic monitoring was carried out to identify patterns of coral spawning. Our results suggest the sharpest temperature increases and full moon timing have the biggest influence on the month and day of coral spawning, whereas the tidal cycle influences the hour when gametes are released. Coral spawning peaks were observed to occur in two seasons, April and October-November, 5-7 days after full moon and 2-3 hours after sunset during falling tides. The presence of two spawning seasons may provide coral reefs at the Banda Islands with an advantage to recover from potential impacts, such as storms, bleaching or destructive fishing.